Polypharmacy and associated factors among patients with type two diabetes mellitus with comorbidity: a multicenter cross-sectional study in Northwest Ethiopia - Fasil Bayafers Tamene; Tirsit Ketsela Zeleke; Akalu Fetene Desalew; Getachew Yitayew Tarekegn; Ashenafi Kibret Sendekie; Selamawit Mengstu Tafere; Mekdes Kiflu; Tilaye Arega Moges; Fisseha Nigussie Dagnew; Samuel Agegnew Wondm (BMC Endocrine Disorders)
Abstract Background Patients with Diabetes Mellitus (DM) may have various comorbid illnesses, which necessitates the prescription of multiple drugs. Polypharmacy can raise the risk of adverse drug events, drug interactions, and medication non-adherence, even though using numerous medications is not always inappropriate. The aim of this study was to assess the rate of polypharmacy and associated factors among patients with Type 2 Diabetes Mellitus (T2DM) with comorbidity in Northwest Ethiopia. Methods A cross-sectional study was conducted among 409 T2DM patients with comorbidity in Northwest Ethiopia from April 1 to June 30, 2023. A consecutive sampling technique was used to enroll study participants. Data were entered using EpiData version 4.6.0 and analyzed with SPSS version 26. Polypharmacy was determined by reviewing the number and type of medications based on relevant evidence. A multivariable logistic regression model was fitted to identify factors associated with polypharmacy. Variables with a p-value less than 0.05 at a 95% confidence interval were considered statistically significant. Results The prevalence of polypharmacy was 59.1%. Duration of illness (AOR = 2.06, 95% CI: 1.14, 3.07) hypoglycemia (AOR = 2.75, 95% CI: 1.45, 5.21) and comorbidity of four, five or more (AOR = 2.19, 95% CI: 1.16, 4.15), (AOR = 3.23, 95% CI: 1.47, 7.09) were significantly associated with polypharmacy. Conclusion and recommendation In this study, more than half of the participants were found to be on polypharmacy. Patients with longer duration of illness, hypoglycemia and multiple comorbidities need routine follow-up to reduce the rate of polypharmacy.